(untitled) (Third Sector Social Economic Review, 2023)
Objective: To evaluate the nutritional knowledge levels, prejudices against obesity and food choices of X, Y, Z generations. Method: A questionnaire consisting of Nutrition Knowledge Level Scale For Adults (NKLSA), Obesity Prejudice Scale (GAMS-27), Food Choice Questionnaire (FCQ) in order to measure the nutritional knowledge level of the participants with questions about sociodemographic characteristics and eating habits of the participants face to face has been applied. The obtained data were analyzed in SPSS v26 (IBM Inc., Chicago, IL, USA) program. Results: The mean age of the X, Y, and Z generations was 48.92±4.68 years, 34.06±5.14 years, 18.90±1.31 years, and 18.90±1.31 years, respectively; The mean BMI are 27.27±3.25 kg/m2, 26.30±3.69 kg/m2, and 23.01±3.74 kg/m2, respectively. The “GAMS-27 Total” score was found to be statistically higher in generation Y than in other generations (H=14.980; p<0.01). “Mood” (H=8.282; p<0.05), “Convenience” (H=18.105; p<0.001), “Sensory Appeal” (H=10.068; p<0.01) and “Price” from BSA sub-factors (H=9.631; p<0.01) sub-factors score medians were highest in Z generation individuals; Median score for the sub-factors “Natural Content” (H=29.287; p<0.001), “Weight Control” (H=9.396; p<0.01), and “Ethical Concern” (H=11.209; p<0.01) It was found the highest in X generation individuals. The increase in NKLSA’s ""Basic Nutrition"" sub-factor scores resulted in an increase in FCQ’s ""Health"", ""Mood"", ""Sensory Appeal"", ""Natural Content"", ""Price"" sub-factor scores (p<0.05); The increase in NKLSA’s ""Food Preference"" sub-factor scores resulted in a decrease in FCQ’s ""Health"", ""Convenience"", ""Sensory Appeal"", ""Natural Content"", ""Price"", ""Weight Control"", ""Familiarity"" sub-factor scores ( p<0.05) and the increase in the “GAMS-27 Total” scores, FCQ’s “Health”, “Mood”, “Convenience”, “Sensory Attraction”, “Natural Content”, “Price”, “Weight Control” and It was found that ""familiarity"" (p<0.05) caused a decrease in sub-factor scores. Conclusion: The generation with the highest prejudice against obesity; It is the Y generation. Nutritional knowledge and obesity bias of generations affect food choices.